Agriculture negotiators reach agreement at COP23 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
CCAFS’s research and engagement were instrumental in supporting the UNFCCC COP23 decision on the Koronivia Joint Work on Agriculture. CCAFS provided scientific evidence on the importance of agriculture to the Paris Agreement goals, analysis of mitigation and adaptation in the NDCs, and concrete technical and policy options for addressing agriculture in UNFCCC negotiations, and convened workshops that negotiators cited as critical to enabling them to formulate their positions and come to an agreement.